MENINGKATKAN KEMAMPUAN MENULIS TEKS PENGUMUMAN MENGGUNAKAN BAHASA EFEKTIF SISWA KELAS 7C SMPN 2 KRIAN SIDOARJO DENGAN TEKNIK P2LT - Anggarini, Lusi; Pramujiono, Agung (Universitas PGRI Adi Buana Surabaya, 2014)
Abstract Learning is an activity that uses the connection information and the environment by planning for students. To make the ease in learning to improve writing skills by using the announcement effectively, Indonesia language teachers should make learning an active, creative, and fun. This study has the objective to improve the skill of writing an announcement by using effective techniques of Presentation of Discovery Continuous Exercise (P2LT). The subject of this research is the studens of SMPN 2 Krian, Sidoarjo, grade 7, grade 7-C in particular. Before learning of the class done, researchers and language teacher conducting the initial orientation of Indonesia. Based on early reflection, researchers know that the expertise of writing grade 7-C student at SMPN 2 Krian, Sidoarjo, still low. Their score was 64,51. This issue has been resolved by using the techniques of P2LT. Based on analysis conducted after the activity, an increase in comparison to the initial condition the average of 23%. Average score announcement text writing skills of students of initial conditions to the first cycle ride 11.7, while achievement of KKM 54,1 ride. Writing skills score announcements in the first cycle of 77,23, whereas in the second cycle is 80,20. Average cumulative a score of the ability to write the text of an announcement from the cycle first into the cycle of rising 3,99, both while the attainment of kkm from the cycle first into a cycle second increased by 17.88.Thus can be inferred that the implementation of technical P2LT can improve the ability to write the text of the nnouncement of a student 7-C SMPN- 2 Krian. Key words: skill, Announcement text, P2LT